Student evaluation surveys: anonymous comments that offend or are unprofessional - Tucker, Beatrice (Springer, 2014)
© 2014, Springer Science+Business Media Dordrecht. Student comments are routinely collected in university evaluation surveys for the purpose of improving teaching and learning. Whilst student comments provide valuable insights into their experiences, there is limited published research reporting the extent to which student comments are offensive and professional. The aim of this study was to investigate the number of student comments that were identified as being offensive or unprofessional in an online unit evaluation survey collected in a semester in 2010 from an Australian university. One person read 30,684 comments taken from 17,855 surveys and identified comments considered to be abusive or unprofessional. Comments were categorised as either abusive or unprofessional and by the intended target (that is, teacher, unit, resource). Thirteen abusive comments (0.04 % of the sample) were identified. Five abusive comments were directed at the teacher and eight were targeted at teaching and learning experiences. Forty-six comments (0.15 % of the sample) were identified as unprofessional. Of these, seven comments were directed at the teacher and 34 were about units. This suggests that the vast majority of students do not abuse the privilege of giving anonymous feedback. Strategies identified in this paper to educate students and give appropriate feedback can be adopted by universities to minimise offensive comments. Universities can educate students and teachers in appropriate and professional ways of working together, in providing professional feedback to improve the student experience in teaching and learning and to support and mentor teachers in their academic careers.